Interpersonal, intertemporal and spatial variation in risk perceptions: evidence from East Africa - Cheryl Doss; John McPeak; Christopher Barrett (Yale University, Economic Growth Center, 2006)
This study investigates variation over time, space and household and individual characteristics in how people perceive different risks. Using original data from the arid and semi-arid lands of east Africa, we explore which risks concern individuals and how they assess their relative level of concern about these identified risks. Because these assessments were gathered for multiple time periods, sites, households and individuals within households, we are able to identify the degree to which risk perceptions vary across time, across communities, across households within a community, and across individuals within a household. We find the primary determinants of risk rankings to be changing community level variables over time, with household specific and individual specific variables exhibiting much less influence. This suggests that community based planning and monitoring of development efforts that address risk exposure should be prioritized. We also find that individuals throughout this area are most concerned about food security overall, so that development efforts that directly address this problem should be given the highest priority.
Keywords: O12; D80; Q0; 330; Risk ranking; risk perceptions; intrahousehold; Africa; Kenya; Ethiopia